Structure and Depth Study of a Reflector Appears on 52-Seismic Sections in Um-Al-Anz Area, Weastern Desert, Iraq. - Aziz, Bakhtiar (Iraqi Journal of Science, 2025)
A reflector was picked on (52) selarnic sections, (2960 km lengthi, in Um-Al-Anz area, western desert. It has two way time ranges between (2940-3700) msee. The reflector was identified throught correlating and tying the seismic sections of the surrounding area. The reflector represent the reflection from near top of the basement and most probably it was from a limestone bed (Cambrian age) which is covered the crystalline hasement Seismic maps, (Isochron, Velocity, and Depth), have been constructed for the reflector. The depth map shows that the reflecter depths range between (6040-7600) m with respect to sea level. The general dip is soward west and southeastern. In structural point of view the present study denote to the existence of a very huge anticline in the western desert trending NIOW, It has length and width range between (130 x 75) km. The depth map also shows the apperance of several anticlines have different dimension and eloures. They have great importance in possibility of petroleum existence. Finally parts of the two majoe faits, Abs-jeer and Umage-Samaru-Halabja, have been detected and plotted on the Isochron, and depth maps.